Relationship between compassion fatigue and self-care in Portuguese psychologists - Tavares, Francisca; Fonte, Carla (Pensando Psicología, 2025)
Effective professional performance in psychological practice has been increasingly associated with self-care strategies, which the literature highlighted as essential for promoting psychologists’ well-being and preventing compassion fatigue. In this context, the present study aims to analyze the relationship between compassion fatigue and self-care in a sample of 106 participants, consisting of psychologists aged between 22 and 61 years, M = 31.11 (SD = 8.12). Data were collected using a sociodemographic questionnaire, the Professional Quality of Life Scale, and the Self-Care Assessment Scale for Psychologists. The results suggest that participants report high levels of compassion satisfaction, professional support, and professional development. Conversely, low levels of burnout, secondary traumatic stress, life balance, cognitive strategies, and daily balance were observed. Furthermore, the findings indicate that individuals who engage in supervision and peer consultation as self-care strategies exhibit higher levels of compassion satisfaction. These results are significant for understanding the concept of compassion fatigue and highlight the effectiveness of peer consultation and supervision in promoting the well-being of psychologists.